Development of a multi-residues method for the analysis of pesticides in peper (piper nigrum) - Ching, Lee Fung (University Malaysia Sarawak, UNIMAS, 2015)
A rapid, specific and sensitive multi-residues method has been developed for the analysis of 6 pesticides in black pepper based on the Quick, Easy, Cheap, Effective, Rugged and Safe (QuEChERS) solid-phase extraction (SPE) sample preparation method. In this work, QuEChERS method, which was originally developed for vegetable samples with high amount of water, was modified to improve the extraction of a wide range of pesticides in dried product such as black pepper. The residues are extracted from the sample with acetonitrile. The extracted organic phase containing the pesticides was further clean-up by eluting with miniaturized carbon activated column (for organophosphorous pesticides) or silica column (for organochlorine pesticides). The SPE method was chosen because less solvent is used, time for clean up can be significantly reduced and cross contamination can be minimized. The final extracts were analyzed by gas chromatography (GC) equipped with flame photometric detector (FPD for organophosphorous pesticides) or electron capture detector (ECD for organochlorine pesticides) or high performance liquid chromatography (HPLC) equipped with ultra-violet detector (for benomyl). The recoveries of pepper samples spiked at 0.1, 0.5 and 1.0 mg kg-1 were between 60% to 75% with relative standard deviation (RSD) of less than 8%. This extraction method provided a well-defined phase separation without dilution and achieved acceptable recoveries. This method was applied for screening of pesticide residues in peppers from Balai Ringin, Semongok and Malaysia Pepper Board.